2019
DOI: 10.1186/s10020-019-0131-0
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 concentration measurements in trauma patients: assessment of pre-analytical conditions and sample material

Abstract: BackgroundHMGB1 is a mediator of systemic inflammation in sepsis and trauma, and a promising biomarker in many diseases. There is currently no standard operating procedure for pre-analytical handling of HMGB1 samples, despite that pre-analytical conditions account for a substantial part of the overall error rate in laboratory testing. We hypothesized that the considerable variations in reported HMGB1 concentrations and kinetics in trauma patients could be partly explained by differences in pre-analytical condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…TLR4 recognizes DAMPs [ 13 ], which are associated with host cell components released after cell damage [ 5 , 14 , 15 ]. We revealed that levels of certain DAMPs, including HMGB1, S100A8, and S100A9, were elevated after blood mixing, and this finding was corroborated by other reports [ 16 , 17 , 18 , 19 , 20 ] on blood transfusions ( Figure 3 ). For example, first, a transfusion of red blood cells increases vulnerability to lung inflammation through HMGB1 release and induces lung endothelial cell necroptosis [ 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…TLR4 recognizes DAMPs [ 13 ], which are associated with host cell components released after cell damage [ 5 , 14 , 15 ]. We revealed that levels of certain DAMPs, including HMGB1, S100A8, and S100A9, were elevated after blood mixing, and this finding was corroborated by other reports [ 16 , 17 , 18 , 19 , 20 ] on blood transfusions ( Figure 3 ). For example, first, a transfusion of red blood cells increases vulnerability to lung inflammation through HMGB1 release and induces lung endothelial cell necroptosis [ 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…A potentially important discrepancy between HMGB1 levels in arterial and venous plasma samples was recently discovered in trauma patients (Ottestad et al 2019a). Arterial HMGB1 concentrations were consistently lower than venous concentrations in simultaneously obtained samples (arterial = 0.60 x venous; 95% CI 0.30-0.90).…”
Section: Ragementioning
confidence: 99%
“…In the case of HMGB1, significantly lower concentrations were obtained in EDTA plasma than in serum (± gel) with a mean difference of 1.37−3.82 ng/mL (p = 2.94 × 10 −2 to p = 1.48 × 10 −3 ) at all time points, which represents a 4-to 12-fold mean difference compared to the median HMGB1 concentration in plasma (0.29−0.35 ng/mL). The results for HMGB1 confirmed previously reported differences in HMGB1 concentrations between serum and plasma presented by Weng et al 16 Notably, Ottestad et al 29 showed a strong correlation between serum and plasma but wide limits of agreement with an increasing HMGB1 concentration. This study reported increasing mean differences between serum and plasma, thus highlighting a bias between matrices in samples with a high HMGB1 concentration.…”
Section: Effects Of Sample Matrix On Dili-analytesmentioning
confidence: 99%
“…Compared to serum (± gel) results, HMGB1 concentrations remain more stable in EDTA plasma with a mean decrease of 8% ± 36% (mean ± SD). These findings agree with data reported by Ottestad et al, presenting stable HMGB1 concentrations in EDTA plasma for up to 6 h of benchtop time before centrifugation, 29 while exponential increases in HMGB1 concentrations were observed after 6 h of benchtop time, suggesting complete processing until at °C within this time even for EDTA plasma. For ccK18, slightly higher concentrations and higher variations in concentration levels were observed in serum (± gel) than in plasma.…”
Section: Effects Of Sample Benchtop Time On Dili-analytesmentioning
confidence: 99%